1994
DOI: 10.1021/bp00030a009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modulated Glucose Uptake on High‐Level Recombinant Protein Production in a Dense Escherichia coli Culture

Abstract: Methyl alpha-glucoside (alpha-MG) is a metabolically inert glucose analog sharing the same phosphotransferase system with glucose. The potential of using this compound, which acts as a nontoxic competitive inhibitor, to modulate glucose uptake and subsequently reduce the acetate accumulation rate was investigated. In a complex medium, no significant effect on the growth rate was observed when the alpha-MG to glucose ratio was low. The effect of alpha-MG supplementation on the production of a model recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 9 publications
(10 reference statements)
1
35
2
Order By: Relevance
“…It is argued that a properly designed new reaction pathway will perturb the existing pathway networks positively and will result in a better strain with the desired cellular characteristics . Two different approaches have been investigated to modulate the glucose uptake rate in E. coli (Chou et al, 1994a;Chou et al, 1994b). In the first study, methyl α-glucoside (α-MG), a glucose analog, which shares the same phosphotransferase system (PTS) was used to modulate the glucose uptake rate.…”
Section: An Example Of Metabolic Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…It is argued that a properly designed new reaction pathway will perturb the existing pathway networks positively and will result in a better strain with the desired cellular characteristics . Two different approaches have been investigated to modulate the glucose uptake rate in E. coli (Chou et al, 1994a;Chou et al, 1994b). In the first study, methyl α-glucoside (α-MG), a glucose analog, which shares the same phosphotransferase system (PTS) was used to modulate the glucose uptake rate.…”
Section: An Example Of Metabolic Engineeringmentioning
confidence: 99%
“…This compound is a nontoxic, metabolically inert, competitive inhibitor to enzyme II glc of the PTS. The glucose analog addition resulted in a reduced acetate accumulation in the reactor and subsequently led to a significant enhancement in recombinant protein production (Chou et al, 1994a). Based on the results from this study, a metabolically engineered E coli strain with reduced acetate synthesis rate was constructed through the modification of glucose uptake rate (Chou et al, 1994b).…”
Section: An Example Of Metabolic Engineeringmentioning
confidence: 99%
“…Further, acid production was undetectable in the glucose-citrate cultures. Subsequent work showed that productivity of recombinant protein (units of protein/vol of culture-time) in glucose-citrate medium was 5-to 10-fold higher (26), further emphasizing the utility of reducing acid production.Although there have been several efforts to reduce acid formation in E. coli by metabolic engineering (6,8), there has been no report on metabolic engineering of B. subtilis. Based on measurements and theoretical analyses, we identified pyruvate kinase (PYK) as the activity most likely affected by growth in glucose-citrate medium (12,15).…”
mentioning
confidence: 99%
“…Although there have been several efforts to reduce acid formation in E. coli by metabolic engineering (6,8), there has been no report on metabolic engineering of B. subtilis. Based on measurements and theoretical analyses, we identified pyruvate kinase (PYK) as the activity most likely affected by growth in glucose-citrate medium (12,15).…”
mentioning
confidence: 99%
“…This second potential site of flux regulation also provides a "safety valve" for checking triose pool increases in response to the PYK bottleneck. Furthermore, the elevation of glucose-6-phosphate suggests that precursor supply for NADPH production by the HMP pathway is not threatened, which could conceivably result if the PTS system were downregulated (Chou et al 1994).…”
Section: Discussionmentioning
confidence: 99%